An in vivo pharmacological study: Variation in tissue-accumulation for the drug probucol as the result of targeted microtechnology and matrix-acrylic acid optimization and stabilization techniques - Mooranian, Armin; Zamani, Nassim; Takechi, Ryu; Luna, Giuseppe; Mikov, M.; Goločorbin-Kon, S.; Elnashar, Magdy; Arfuso, Frank; Al-Salami, Hani (PUBLIC LIBRARY SCIENCE, 2019)
© 2019 Mooranian et al.